2014
DOI: 10.1080/15374416.2014.910790
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Client Outcomes for Two Evidence-Based Treatment Consultation Strategies

Abstract: Posttraining expert case consultation is a key component of transporting and scaling up evidence-based treatments, and hopefully retaining their efficacy. Live practice observation and in vivo coaching is a strategy used in academic training environments, but is rarely feasible in field settings. Post hoc telephone consultation is a substitute strategy but does not approximate many aspects of live coaching. Live video technology offers a closer approximation but has not yet been sufficiently tested. Using a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“… 119 A more recent study found that live video coaching resulted in small but meaningful improvements in client outcomes compared with traditional phone consultation. 120 …”
Section: Methodsmentioning
confidence: 99%
“… 119 A more recent study found that live video coaching resulted in small but meaningful improvements in client outcomes compared with traditional phone consultation. 120 …”
Section: Methodsmentioning
confidence: 99%
“…This observation also supports another core tactic of the ICT strategy, the effectiveness of ongoing coaching during the immediate post-training months. Ongoing in vivo coaching has been demonstrated to offer advantages over alternative post-training quality control and competency development strategies in randomized trials with both the SafeCare curriculum and others types of behavioral services (Chaffin et al 2012a; Funderburk et al 2014). Drift occurs easily in EBT implementations.…”
Section: Discussionmentioning
confidence: 99%
“…Coaching uses a CBT training expert to attend in person to observe group sessions led by the SPs, provide live feedback [66, 67], and model the use of core CBT elements to improve SP competence [65, 6872]. All SPs from schools randomized to coaching in phase 1 will receive weekly visits from a CBT coach for a minimum of 12 weeks, which will occur in the context of the SPs weekly CBT group.…”
Section: Methodsmentioning
confidence: 99%